'Financial Consumerism': citizenship, consumerism and capital ownership in the 1980s. Issue 2 (3rd April 2017) - Edwards, Amy
Abstract: Popular capitalism provides a useful case study to reveal the overt mechanisms of Thatcherism as well as the concealed and coincidental. The Party's programmes of council house sales and privatisation have rightly been understood as a central part of popular capitalism. However, Thatcherism relied on far more than just the actions of the Conservative Party alone. This article explores the role of financial institutions in creating an institutional framework which enabled the British public to engage with popular capitalism. In doing so it builds on existing work on Thatcherism as a political and cultural project by considering both the ideological and institutional mechanisms through which economic elements of Thatcherism were normalised. In particular it explores the term 'financial consumerism' as a useful moniker for Thatcherism which moves beyond popular capitalism and allows a consideration of wider questions about consumer society, participation and social inclusion.